The Development of the Ideas of Indo–European Homeland - Mickevičienė, Diana (Acta Orientalia Vilnensia, 2000)
The issue of the Indoeuropean homeland was always relevant in different cultures. The ideas of Indoeuropean homeland have developed in severai directions – academic theories, popular ideas of intellectuals and “folksmen”. But they were interconnected and influencing each other. The purpose of this article is to review the development of the ideas of Indoeuropean homeland in three different but related to the issue cultural backgrounds: Western Europe, Lithuania and India, and to reveal the impact of the epochs and regions on the public and scholarly ideas. The very definition of Indoeuropeans is a problem which is characteristic of whole course of development of Indo–European studies which is reviewed here with regard to researches of the homeland. Apart from many scientific theories of homeland and attempts to locate it (ranging from as far south as Indus valley to the North Pole), there existed and exist a wide range of opinions on homeland in each society discussed. After analysing the three societies some generalisation can be done: while Europeans in the past tended to relate themselves to homeland through their “Indoeuropean” versus “non–Indoeuropean” (that can mean non–European) identity, but are not preoccupied with the issue now, Lithuanians are still concerned with the issue of homeland, but from the angle of the antiquity of the homeland and special role of Lithuanians there. And Indians are now especially concerned with both the issue of Aryan identity, its relation to “Indoeuropean”, “European” identity and the antiquity of the homeland with the special role of the Aryans in it.